The relationship between stigma and anxiety among nurses during COVID-19 pandemic - Marnila Yesni; Dwi Yunita Rahmadhani (Palembang MediRose Publisher, 2022)
Background: Puskesmas as public health facility encounter challenges in facing COVID-19, including nurses who provides care for patients who faces challenges in this emergency. The frequent interaction of nurses with patients put nurses in a high risk of being exposed to COVID-19. This situation triggers a negative stigma towards nurses in the community which impacted a lot of nurses. Purpose: The purpose of this study is the relation between anxiety level and stigma on nurses during the COVID -19 pandemic. Methods: The study used a descriptive analytic study with a cross-sectional study design with 96 respondents from Puskesmas Jambi City. Statistical test used in this research is Chi Square. Results: Statistical test result shows that there is a significant relation between stigma and anxiety on nurses in Puskesmas Jambi city with p value=0.001. Conclusions: Nurses are COVID-19 front liners, who are always exposed with patients, along with the stigma that comes from the community. The stigma could affect the nurses psychologically. Therefore, more attention is needed regarding this matter. Increasing public knowledge regarding infectious disease is one of the first steps in handling this issue as it could change the public perception regarding COVID-19 and its urgently needed to eliminate the negative stigma against nurses. for the next study, it can be a reference and research more about other factors that cause anxiety in nurses during the COVID-19 pandemic